A Mike & Riel Mystery: Hit and Run - Book 1 - McClintock, Norah (Minneapolis : Darby Creek, 2014)
"Fifteen-year-old Mike McGill has been living with his Uncle Billy since his mother's death. Only ten years older than Mike, Billy loves to party, and doesn't pay much attention when Mike starts getting in trouble. But Mike's history teacher, an ex-cop name Riel, does pay attention. Especially when long-hidden information starts coming to light that makes it seem that the death of Mike's mother might not have been an accident after all"--
Keywords: Mothers -- Juvenile fiction -- Death; Uncles -- Juvenile fiction; Ex-police officers -- Juvenile fiction; Teachers -- Juvenile fiction; Mothers -- Fiction -- Death; Uncles -- Fiction; Ex-police officers -- Fiction; Teachers -- Fiction; Mystery and detective stories